2017
DOI: 10.1186/s12891-017-1711-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and correlation with clinical and radiographic variables in patients with ankylosing spondylitis: a retrospective case series study

Abstract: BackgroundPreviously, many studies have evaluated quality of life (QoL) in patients with ankylosing spondylitis (AS), however, none of them specifically investigated the correlation between pain-related disability measured by Oswestry Disability Index (ODI) and QoL in AS patients. In addition, the correlation between global kyphosis (GK) in lateral plain radiographs and QoL in AS patients remains unclear up to now. Therefore, this study aimed to evaluate QoL and correlation with clinical and radiographic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
(53 reference statements)
3
19
0
Order By: Relevance
“…Only a few previous studies have addressed if there is a relation between radiographic changes in the spine and HRQoL in AS. A Chinese study conducted in 245 patients with AS found that patients with severe kyphosis had a significantly worse PF domain score compared to patients with milder kyphosis [10]. In a study of 962 patients with AS, Bodur et al identified weak but significant inverse correlation between the Bath Ankylosing Spondylitis Radiology Index (BASRI) and some of the SF-36 domains (PF, GH and MH) [29] similar to findings in a study of 100 patients with AS from Morocco [30].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few previous studies have addressed if there is a relation between radiographic changes in the spine and HRQoL in AS. A Chinese study conducted in 245 patients with AS found that patients with severe kyphosis had a significantly worse PF domain score compared to patients with milder kyphosis [10]. In a study of 962 patients with AS, Bodur et al identified weak but significant inverse correlation between the Bath Ankylosing Spondylitis Radiology Index (BASRI) and some of the SF-36 domains (PF, GH and MH) [29] similar to findings in a study of 100 patients with AS from Morocco [30].…”
Section: Discussionmentioning
confidence: 99%
“…Ankylosing spondylitis (AS) is chronic inflammatory arthritis characterized by ankylosis of the spine and sacroiliac joint [1]. Spinal ankylosis in AS causes functional disability, resulting in a socioeconomic loss at a young age [2]. Recently, tumor necrosis factor (TNF) inhibitors have been considered as an effective treatment for AS; however, despite their wide use, it remains uncertain whether TNF inhibitors can prevent spinal progression [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Each domension is scored ranging from 0 to 100, higher scores indicating better QoL [4]. This scale has been translated into different language versions and validated in patients with AS [4,27]. In this study, the Cronbachs' a of total score was 0.87, and the Cronbachs' a of each domension ranged from 0.777 to 0.915.…”
Section: Quality Of Lifementioning
confidence: 88%